α-amanitin induces hepatotoxicity via PPAR-γ inhibition and NLRP3 inflammasome activation - Haowei Wang; Huijie Zhang; Lin Miao; Chan Wang; Hanxin Teng; Xiaodong Li; Xiaoxing Zhang; Genmeng Yang; Shangwen Wang; Xiaofeng Zeng (Ecotoxicology and Environmental Safety)
Mushroom poisoning, predominantly caused by α-amanitin, is a critical food safety concern in worldwide, with severe cases leading to hepatotoxicity and fatalities. This study delves into the hepatotoxic effects of α-amanitin, focusing on the NLRP3 inflammasome and PPAR-γ's regulatory role in inflammation. In vitro studies with L-02 cells showed that α-amanitin reduces cell viability and triggers NLRP3 inflammasome activation, increasing NF-κB phosphorylation and pro-inflammatory cytokines IL-18 and IL-1β. The NLRP3 inhibitor MCC950 mitigated these effects without impacting NF-κB. Conversely, PPAR-γ knockdown intensified the inflammatory response. In vivo, α-amanitin induced dose-dependent liver injury in mice, evident by elevated serum ALT and AST, and histological liver damage. MCC950 pretreatment offered protection against hepatotoxicity, while PPAR-γ inhibition with GW9662 worsened the condition. The study highlights the interplay between α-amanitin, NLRP3, and PPAR-γ in hepatotoxicity, proposing potential therapeutic targets for mushroom poisoning-induced liver diseases.